Modeling and control of unmanned aerial/underwater vehicles using hybrid control. (July 2018) - Mercado Ravell, Diego Alberto; Maia, Marco Moreno; Diez, Francisco Javier
Abstract: Modeling and control of a multi-medium unmanned vehicle capable of seamless operation in air or underwater is introduced in this paper. The multi-medium system is treated as a hybrid system with continuous dynamics while performing in both air and underwater, and discrete jumps in the medium density during the transitions. The continuous dynamics are modeled by the Newton–Euler formalism, taking into account the effects of the buoyancy and drag phenomena, normally neglected in aerial vehicles. A hybrid controller is designed for trajectory tracking considering the full system, including a transition strategy to assure the switching between mediums. Stability analysis for the full system is provided using hybrid Lyapunov and invariance principles. The performance of the control strategy is validated through simulations. Finally, an experimental platform consisting of a multirotor in an octo-quadcopter configuration was developed and some preliminary experimental results are introduced, showing the vehicle performing in air, underwater and through the transition. Highlights: Hybrid systems are used to model the unmanned multi-medium vehicle. The abrupt change of density is treated as a discrete jump in the dynamics. Hybrid control theory is used for control design and stability proof. As a proof of concept, preliminary real time experimental results are provided. Experimental results demonstrated smooth transitions between mediums.